Translation, Validity, and Reliability of Depression Literacy Questionnaire in Iranian Young Adults - Fatteme Raiisi; Mohamad Ebrahimi; Fahimeh Ghahvehchi_Hosseini; Kosar Jafari; Fatemeh Rahmati (International Journal of Preventive Medicine, 2024)
Background: Depression literacy has notable advantages in the early identification and treatment of depression. The current study was conducted with the aim of translating and investigating the validity and reliability of the Depression Literacy Questionnaire (D-Lit) in Iranian young adults. Methods: The current study entailed a descriptive-analytical study in which the translation, validation, and preparation of the Persian version of D-Lit were conducted. It had two stages: translation and validation. In order to check the composite reliability, the statistical population consisted of Iranian adults in the city of Mashhad, and 300 people participated in this study in the form of a census. The content validity ratio (CVR) and content validity index (CVI) indices were used for content validity. Results: The results of the content validity evaluation of this questionnaire indicated that both the CVR and CVI indices have higher-than-average coefficients (0.78 and 0.83). Furthermore, the Cronbach’s alpha value for the components of the D-Lit was found to be higher than 0.70. In the present study, the questionnaire’s reliability was assessed using the intra-cluster correlation coefficient (ICC), and the difficulty coefficient for the whole questionnaire and its sub-components was at a favorable level. Out of 22 questions, 17 questions of this questionnaire were retained and questions 1, 17, and 22 were removed due to low CVR and CVI in the validity stage, and questions 5 and 13 were removed due to common factor load in the factor analysis stage. Conclusion: According to the content validity and reliability in this study, this tool can be used to identify underlying factors, etiology, and treatment of depression.